Ambient Fine Particulate Matter Alters Cerebral Hemodynamics in the Elderly - Wellenius, Gregory A.; Boyle, Luke D.; Wilker, Elissa H.; Sorond, Farzaneh A.; Coull, Brent A.; Koutrakis, Petros; Mittleman, Murray A.; Lipsitz, Lewis A. (Stroke (1970), 2013)
Short-term elevations in fine particulate matter air pollution (PM2.5) are associated with increased risk of acute cerebrovascular events. Evidence from the peripheral circulation suggests that vascular dysfunction may be a central mechanism. However, the effects of PM2.5 on cerebrovascular function and hemodynamics are unknown. We used transcranial Doppler ultrasound to measure beat-to-beat blood flow velocity in the middle cerebral artery at rest and in response to changes in end-tidal CO2 (cerebral vasoreactivity) and arterial blood pressure (cerebral autoregulation) in 482 participants from the Maintenance of Balance, Independent Living, Intellect, and Zest in the Elderly (MOBILIZE) of Boston study. We used linear mixed effects models with random subject intercepts to evaluate the association between cerebrovascular hemodynamic parameters and mean PM2.5 levels 1 to 28 days earlier adjusting for age, race, medical history, meteorologic covariates, day of week, temporal trends, and season. An interquartile range increase (3.0 µg/m(3)) in mean PM2.5 levels during the previous 28 days was associated with an 8.6% (95% confidence interval, 3.7%-13.8%; P<0.001) higher cerebral vascular resistance and a 7.5% (95% confidence interval, 4.2%-10.6%; P<0.001) lower blood flow velocity at rest. Measures of cerebral vasoreactivity and autoregulation were not associated with PM2.5 levels. In this cohort of community-dwelling seniors, exposure to PM2.5 was associated with higher resting cerebrovascular resistance and lower cerebral blood flow velocity. If replicated, these findings suggest that alterations in cerebrovascular hemodynamics may underlie the increased risk of particle-related acute cerebrovascular events.